Isolation and identification of fungi with potential for biological control of Asiatic corn borer, Ostrinia furnacalis (Guenee) - Escrupolo, Mishelle P. (2002)
Six cornfields from COMVAL having different corn borer infestation level were randomly selected for collection of specimen. Most of the fungi isolated were from corn borers collected in areas with high level of infestation except for one, the km 94 isolate. The first batch collected corn borer larvae were placed in petri plates containing filter paper moistened with distilled water and incubated for seven days. The fungal growth observed from the insect?s body were isolated, purified, and cultured on a Potato Dextrose Agar (PDA) medium. Identification of the isolates was done using a dichotomous key by Raymundo et.al. (1991). Two of the five isolates were identified belonging to genus Rhizopus while the remaining three belong to genus Aspergillus. The second batch of collected corn borer larvae were reared up to the third generation but a bioassay was not performed due to some constraints. Bioassay of the fungal isolates against corn borer must be done to determine its potential for biological control of the host insect
Thesis (BS Biology) -- University of the Philippines Mindanao, 2002